Fighting Discrimination: History, Strategies, and Social Movements of Sunda Wiwitan - Khoirul Basyar; Abdul Hamid (JURNAL PENELITIAN, 2025)
This paper aims to capture the resistance of the marginalized Sunda Wiwitan community against the hegemony of the majority religion, in order to survive. In collecting data, this study uses literature from previous research, as well as direct observations and interviews with key figures from the Sunda Wiwitan community. The analysis is based on the theory of New Social Movements, which has been widely discussed by scholars. The study concludes that throughout the three leadership periods of Sunda Wiwitan, all have faced discrimination. This discrimination comes from the state bureaucracy, such as the existence of laws against religious blasphemy, regulations for accepting a religion, unregistered marriages, and more. Discrimination also comes from society, particularly from the orthodox Islamic community, especially from the Darul Islam/Islamic State (DI)/Indonesian Islamic Army (TII) groups (hereafter abbreviated as DI/TII), bullying, and negative stigma with labels such as infidels, heretics, uncircumcised, etc. The difficulties faced by Sunda Wiwitan in finding employment and their limited opportunities for societal development have led them to engage in social movements for survival. These social movements involve reorganizing, reviving the Seren Taun harvest festival, and reconstructing their identity. Based on Erikson's classification, the strategy employed by Sunda Wiwitan is a combination of voice and loyalty. Although their existence is not officially recognized by the state (especially before the Constitutional Court's decision regarding the identity column in ID cards), Sunda Wiwitan does not engage in a frontal movement to separate from the state, but instead creates a strategy of loyalty to the state, while still striving to voice their aspirations.